Building flexible business processes using BPEL and rules : don't embed business policies in your business processes automate them with a business rules engine!. - Afshar, Mohamad
Leading companies are tackling the complexity of their application and IT environments with service-oriented architecture (SOA), which facilitates the development of enterprise applications as modular business services that can be easily integrated and reused, thereby creating a truly flexible, adaptable IT infrastructure. Business process management (BPM) solutions such as those based on Business Process Execution Language (BPEL) enable services to be orchestrated into business processes. Processes built using a BPM solution can be reused, changed easily in response to business requirements and enable real-time process visibility.